Effect of Potassium and Zinc Application on Crop Yield and Uptake of Nutrients in Green gram (Vigna radiata L.) under Coarse Textured Soils - M.K. Jat (Journal of the Indian Society of Soil Science, 2022)
The aim of present study was to find out the optimum dose and application effect of potassium (K) and zinc (Zn) on green gram yield, nodulation, uptake and its build-up/depletion in soil to overcome the production of pulses in Haryana. A series of field experiments were conducted during kharif season from 2018 to 2020 at the Regional Research Station, Chaudhary Charan Singh Haryana Agricultural University (CCSHAU), Bawal, Haryana. The experiment was laid out in a split plot design with four levels of K (0, 10, 20 and 30 kg K2O ha-1) in main plot and Zn (0, 12.5, 25 and 37.5 kg ZnSO4 ha-1) in sub-plot with three replications. The results revealed that application of K significantly affected the yield of green gram up to 20 kg K2O ha-1 whereas Zn application significantly affected the yield of green gram up to 25 kg ZnSO4 ha-1. The interaction between K and Zn was non-significant. The nodules fresh weight and number of nodules per plant increased significantly with the application K whereas, these parameters increased with the application of Zn but results were not significant. The K and Zn application significantly increased their content and uptake in seed and straw of green gram. The available K in soil was influenced by K application but was found to be significant with 20 and 30 kg K2O ha-1. The DTPA extractable Zn content in soil after harvest of crop was also significantly higher with the application of zinc sulphate.